Economic analysis of ceftaroline fosamil for treating community-acquired pneumonia in Spain. (1st February 2020) - Torres, Antoni; Bassetti, Matteo; Welte, Tobias; Rivolo, Simone; Remak, Edit; Peral, Carmen; Charbonneau, Claudie; Hammond, Jennifer; Ansari, Wajeeha; Grau, Santiago
Abstract: Background: Adults admitted to hospital with community-acquired pneumonia (CAP) impose significant burden upon limited hospital resources. To achieve early response and possibly early discharge, thus reducing hospital expenditure, the choice of initial antibiotic therapy is pivotal. Methods: A cost-consequences model was developed to evaluate ceftaroline fosamil (CFT) as an alternative to other antibiotic therapies (ceftriaxone, co-amoxiclav, moxifloxacin, levofloxacin) for the empiric treatment of hospitalized adults with moderate/severe CAP (PORT score III–IV) from the perspective of the Spanish National Health System (NHS). Findings: Compared with ceftriaxone, the model predicted an increase in the number of CFT-treated patients discharged early (PDE) (30.6% vs. 26.1%) while decreasing initial antibiotic failures (3.8% vs. 7.6%). For patients with pneumococcal pneumonia, CFT was cost-saving vs. ceftriaxone (by 1.2%) and significantly increased PDE (32.1% vs. 24.6%). CFT resulted in cost-saving vs. levofloxacin, due lower initial antibiotic therapy costs and increased PDE (30.6% vs. 14.9%). Moxifloxacin and co-amoxiclav early response rate of 53.63% and 54.24% resulted in cost neutrality vs. CFT, with direct comparison hampered by the significantly different early response criteria utilized in the literature. Conclusions: Despite a higher unit cost, CFT is a reasonable alternative to other agents for adults hospitalized with moderate/severe CAP, given the projected higher PDE achieved with similar or lower total costs.